The Influence of Profitability, Liquidity, and Company Growth on Capital Structure and Company Value: A Study of Companies Listed on the LQ45 Index for the 2016-2020 Period - Larosse, Gilang Cempaka; Atma Hayat (Enigma in Economics, 2023)
This research was conducted to test and analyze the effect of profitability on capital structure, liquidity on capital structure, company growth on capital structure, profitability on company value, liquidity on company value, company growth on company value, and capital structure on company value. The type of research is associative quantitative research. This research uses secondary data from the company's annual financial report data published at www.idx.co.id. Deep sample study This numbered 21 companies and sample selection was carried out randomly through purposive sampling. This research uses multiple linear regression analysis with SPSS tools (statistical package for social sciences) version 23. The research results show that liquidity has an effect on capital structure, while profitability and business risk have no effect on capital structure. Capital structure has an effect on company value, while profitability, liquidity, and company growth have no effect on company value.